An Open Trial of a Mind–Body Intervention for Young Women with Moderate to Severe Primary Dysmenorrhea. Issue 7 (5th February 2020) - Payne, Laura A; Seidman, Laura C; Romero, Tamineh; Sim, Myung-Shin
Abstract: Objective: To evaluate the feasibility, acceptability, and preliminary efficacy of a mind–body intervention for moderate to severe primary dysmenorrhea (PD). Design: Open trial (single arm). Setting: Academic medical school. Subjects: A total of 20 young adult women with moderate to severe primary dysmenorrhea were included across four separate intervention groups. Methods: All participants received five 90-minute sessions of a mind–body intervention and completed self-report measures of menstrual pain, depression, anxiety, somatization, and pain catastrophizing at baseline, post-treatment, and at one-, two-, three-, and 12-month follow-up. Self-report of medication use and use of skills learned during the intervention were also collected at all follow-up points. Results: Participants reported significantly lower menstrual pain over time compared with baseline. No changes in anxiety, depression, or somatization were observed, although pain catastrophizing improved over time. Changes in menstrual pain were not associated with changes in medication use or reported use of skills. Conclusions: A mind–body intervention is a promising nondrug intervention for primary dysmenorrhea, and future research should focus on testing the intervention further as part of a randomized clinical trial.